Pelvic Tuberculosis Diagnosed during Operative Laparoscopy for Suspected Ovarian Cancer - Daniel Martingano; Kayla Cagle-Colon; Jeanine Chiaffarano; Alan Marcus; Diana Contreras (Case Reports in Obstetrics and Gynecology)
Background. While the combination of a pelvic mass, very high serum level of CA-125, chest adenopathy, and ascites is concerning for advanced-stage ovarian cancer, the etiology of such a presentation can be due to disseminated pelvic tuberculosis. Case. A 67-year-old para 2 African-American woman presented with abdominal pain and shortness of breath. Subsequent CT and MR imaging demonstrated chest adenopathy, a pelvic mass, omental caking, and ascites. The patient underwent diagnostic laparoscopy with biopsy revealing noncaseating granulomas and subsequent tissue culture revealed Mycobacterium tuberculosis. The patient was diagnosed with disseminated pelvic tuberculosis and multidrug therapy was initiated. Conclusion. Pelvic tuberculosis can mimic advanced-stage ovarian cancer; thus obtaining a tissue sample may be beneficial to more appropriately direct treatment and planning for neoadjuvant therapies given the ineffectiveness of extensive surgical procedures in treating pelvic tuberculosis commonly employed in the treatment of advanced-stage ovarian cancer.